Political and legal studies for the construction of public policies with a human rights approach in Colombia - Gutiérrez-Ossa, Jahir A. (2023)
This paper exposes the role played by the interaction between political and legal studies for the construction of public policies in Colombia by considering human rights approaches. The political and the legal, when shifting from the individual hierarchical sphere to another of complementary functional nature, weigh the construction of public policies with a rights approach. Exploratory, descriptive, and explanatory methods were employed to understand the theoretical role of the political and the legal in the development of public policy agendas, meanwhile, the methodological part was based on the directives, guides, or guidelines of public policies with human rights approaches. A review is made on the state of the art of political and legal studies for the construction of public policies; the evaluation of the criteria of public policies with a focus on human rights based on political and legal studies, and the role played by political and legal studies in the construction of public policies with a focus on human rights in Colombia. An attempt was made to resume the idea of putting rights-based approaches and political-legal governance at the service of democracy under the capacity of the conjugation of political and legal studies with public policies, rights approaches, and political-legal governance.